Knowledge of the pelvic floor in nulliparous women - Neels, Hedwig (J Phys Ther Sci, 2016)
[Purpose] Proper pelvic floor function is important to avoid serious dysfunctions including incontinence, prolapse, and sexual problems. The current study evaluated the knowledge of young nulliparous women about their pelvic floor and identified what additional information they wanted. [Subjects and Methods] In this cross-sectional survey, a validated, 36 item questionnaire was distributed to 212 nulliparous women. The questionnaire addressed demography, pelvic floor muscles, pelvic floor dysfunction, and possible information sources. Descriptive statistics were generated for all variables. Stability and validity testing were performed using Kappa statistics and intra class correlation coefficients to define agreement for each question. The study was approved by the ethics Committee (B300201318334). [Results] Using a VAS scale (0 to 10), the women rated their knowledge about the pelvic floor as a mean of 2.4 (SD 2.01). A total of 93% of the women were insufficiently informed and requested more information; 25% had concerns about developing urinary incontinence, and 14% about fecal incontinence. Many of the women were unaware what pelvic floor training meant. [Conclusion] There was a significant lack of knowledge about pelvic floor function among nulliparous women. The majority of nulliparous women expressed a need for education, which might offer a way to reduce dysfunction.